2005
DOI: 10.1007/s10484-005-2170-2
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Activity During Actual and Mentally Simulated Preparation for Movement

Abstract: The aim of this study was to compare actual versus mentally simulated preparation for a complex motor skill. Two behavioral periods are observed during weightlifting: (i) an initial phase in which the subject standing behind the bar is thought to focus his attention on forthcoming execution and (ii) a second phase between hands/bar contact and execution during which the subject is thought to increase activation. Such mental processes accompanying behavioral sequences are correlated with autonomic nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Studies such as those reported in [28] and [56] suggest that all four ANS-harnessed signals undergo significant changes during mental imagery tasks. More recently, studies have gauged the contribution of each peripheral autonomic signal for mental task classification [58], [59].…”
Section: B Ans Signal Contributionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies such as those reported in [28] and [56] suggest that all four ANS-harnessed signals undergo significant changes during mental imagery tasks. More recently, studies have gauged the contribution of each peripheral autonomic signal for mental task classification [58], [59].…”
Section: B Ans Signal Contributionsmentioning
confidence: 89%
“…Dynamic time warping strategies [57] were investigated but led to no significant performance improvements. As argued in [28] and [56], mental imagery tasks can cause significant increases in skin conductance levels, heart and respiration rates, as well as a decrease in skin temperature. Recent work has also shown significant increases in NIRS raw signal amplitudes during mental imagery tasks [52].…”
Section: A Multimodal Mental State Classificationmentioning
confidence: 92%
See 1 more Smart Citation
“…Overall, based on theoretical background related to CNS organization and on experiments with ANS data recordings, there is now ample evidence of the close link between mental processes and ANS activity. Bolliet et al (2005a) showed strong and rapid tonic heart rate variations in a group of elite weightlifters when they were requested to imagine lifting a bar. They recorded similar physiological patterns during imagined as during actual movement, although to a lesser extent by comparison with actual lifting, as previously underlined.…”
Section: The Autonomic Nervous System: a Witness Of Movement Observatmentioning
confidence: 99%
“…During this mental exercise, the autonomic system responds in a similar manner to actual exercise, even though muscle movement does not actually occur [94]. When elite athletes perform motor imagery of their sport, significant increases are observed in skin conductance levels, heart rate and respiration rate, while skin blood flow, skin temperature and respiration amplitude undergo significant decreases [52,95,96]. The degree of these responses is proportional to the mental effort exerted by the subject.…”
Section: Mental Stimulationmentioning
confidence: 99%